2018
DOI: 10.1111/cei.13115
|View full text |Cite
|
Sign up to set email alerts
|

A quarter of patients with type 1 diabetes have co-existing non-islet autoimmunity: the findings of a UK population-based family study

Abstract: Individuals with type 1 diabetes (T1D) are at increased risk of coeliac disease (CD), autoimmune thyroiditis and autoimmune gastritis, but the absolute risks are unclear. The aim of this study was to investigate the prevalence of autoantibodies to tissue transglutaminase (TGA), thyroid peroxidase (TPOA) and gastric H /K -ATPase (ATPA) and their genetic associations in a well-characterized population-based cohort of individuals with T1D from the Bart's-Oxford family study for whom islet autoantibody prevalence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 62 publications
(106 reference statements)
2
21
0
Order By: Relevance
“…More than 20% of first-degree relatives of patients with type 1 diabetes and ;50% of the relatives with high-risk HLA genotypes developed persistent autoantibodies associated with one of the three autoimmune diseases. Both TGA and thyroid autoimmunity are more frequent in patients with type 1 diabetes, an association that is attributed, in part, to the sharing of susceptible HLA alleles and other genetic susceptibility regions (13)(14)(15). The frequencies of TGA and TPOA in relatives were higher than in previous studies that included predominantly parents of patients with type 1 diabetes (16,18) and were similar to those found in patients with type 1 diabetes (13)(14)(15).…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…More than 20% of first-degree relatives of patients with type 1 diabetes and ;50% of the relatives with high-risk HLA genotypes developed persistent autoantibodies associated with one of the three autoimmune diseases. Both TGA and thyroid autoimmunity are more frequent in patients with type 1 diabetes, an association that is attributed, in part, to the sharing of susceptible HLA alleles and other genetic susceptibility regions (13)(14)(15). The frequencies of TGA and TPOA in relatives were higher than in previous studies that included predominantly parents of patients with type 1 diabetes (16,18) and were similar to those found in patients with type 1 diabetes (13)(14)(15).…”
Section: Discussionsupporting
confidence: 66%
“…These studies have been following newborn children who have a first-degree relative with type 1 diabetes on the basis that they have an elevated risk of developing the disease. Over the course of follow-up, the children were also observed to be at risk for developing other autoantibodies (10,11), similar to findings in patients with type 1 diabetes (12)(13)(14)(15) and in their family members (16)(17)(18). The participants in these studies are now approaching 30 years of age and provide a unique opportunity to track the course of autoimmunity from birth to adulthood.…”
supporting
confidence: 67%
See 1 more Smart Citation
“…The strong association between T1D and CD is associated with a common genetic susceptibility attributed to specific shared alleles, with HLA-DR3-DQ2 and DR4-DQ8 haplotypes increasing the risk of both diseases (24, 25). Interestingly, it has been shown that children with HLA-conferred susceptibility to T1D and CD develop CD-associated antibodies mostly at a younger age or at the same age at which they develop diabetes-associated auto-antibodies (26).…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of HLA class II DRB1*03 was significantly increased in this group compared to 270 sex and age-matched children with type 1 diabetes alone ( p = 0.002). One of the common pathways of autoimmunity in DS, therefore, appears to be mediated through HLA DR3 as has been shown for multiple autoimmunity in type 1 diabetes [ 72 •]. A second is likely to be the Ubiquitin-associated and SH3 domain-containing A ( UBASH3A ).…”
Section: Introductionmentioning
confidence: 99%